Penerapan Model Pembelajaran Berdiferensiasi Di SMKN 1 Surakarta - Farhan Muhammad Rizqi (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
This research aims to find out how far differentiated learning is understood and implemented at SMKN 1 Surakarta, and what is being done to optimize its implementation. This type of research uses qualitative descriptive research with a case study approach. Data sources for this research include informants (deputy head of curriculum and teachers who have implemented differentiated learning), and documents (learning outcomes, flow of learning objectives, teaching modules, student mapping questionnaires). The sampling technique is purposive sampling. Data collection uses interviews, observation and documentation. Testing the validity of the data used is a credibility test (deepening interviews, triangulation of sources and techniques, negative technical analysis, using reference materials, peer discussion), transferability test, dependability test, and confirmability test. This research data analysis uses interactive descriptive techniques. The results of this research are as follows, (1) teachers' understanding regarding differentiated learning still needs to be expanded and improved (2) the implementation of differentiated learning is still not visible (3) teachers have made various efforts to optimize differentiated learning